A splice donor variant in SLAMF1 is associated with canine atopic dermatitis - Forman, Oliver P.; Freyer, Jamie; Kerr, Abigail; Labadie, Julia D.; Denyer, Michael; Gow, Debbie J.; Alexander, Janet; Daya, Michelle; Olivera, Yaindrys Rodriguez; Lozoya, Cecilia; Leutenegger, Christian; Savard, Christian; et al. (Frontiers in Veterinary Science, 2025)
IntroductionCanine atopic dermatitis (CAD) is a common inflammatory skin condition in dogs. It is a lifelong issue that poses a significant welfare concern due to the chronic skin discomfort and pruritus (itching) experienced by affected animals. Excessive scratching, licking, and chewing cause self-inflicted injuries to the skin and increase the risk of secondary infections. Several dog breeds, including Labrador Retriever, Boxer, and French Bulldog, are known to be predisposed to these issues, suggesting a genetic link to the condition.MethodsAccess to a large population of dogs genotyped on a medium-density single-nucleotide polymorphism (SNP) array through commercial Wisdom Panel testing, along with their linked clinical records, allowed a large-scale, highly powered genome-wide association study (GWAS) to be performed. In this study, over 28,000 dogs were examined to identify genetic changes associated with CAD.ResultsA statistically significant signal on canine chromosome 38 was identified, with a particularly strong signal in French Bulldogs. Whole-genome resequencing revealed a compelling splice donor variant in the signaling lymphocytic activation molecule 1 (SLAMF1), a transmembrane receptor with important functions in immune cells. Further analysis of additional genome sequences and RNA samples from the MARS PETCARE BIOBANK confirmed that the SLAMF1 splice variant is a strong potential contributor to an increased risk of atopic dermatitis.DiscussionThe discovery represents the first compelling genetic variant associated with CAD to be validated in more than one breed of dog. The study identifies SLAMF1 as a potential pharmaceutical target and the associated variant as a biomarker to enable dog breeders to make informed breeding decisions to reduce risk of CAD in future generations. The presence of the SLAMF1 variant in many dog breeds and free-roaming dogs worldwide, indicates its potential role in contributing to the global risk of CAD.